Sympathetic contralateral vestibulopathy after unilateral zoster oticus. Issue 5 (1st May 1999) - Schulz, P; Arbusow, V; Strupp, M; Dieterich, M; Sautier, W; Brandt, T
Abstract : A unique case of initially right sided varicella zoster induced Ramsay-Hunt syndrome with complete vestibular loss is reported. The patient subsequently developed deficits of the left vestibule 5 months later. An autoimmune pathogenesis of the left vestibular failure rather than bilateral varicella zoster infection was suggested by the following data: (1) no evidence of vesicular eruptions on the left auricle and the virtual absence of antiviral antibodies after onset of bilateral vestibulopathy; (2) prompt response of the left vestibule to immunosuppressive therapy with corticosteroids; and (3) presence of atypical nervous tissue specific autoantibodies against a 45 kDa protein.